Toxicity of activated-charcoal purified Centella asiatica (L.) Urb. methanolic extract on zebrafish embryos - Maulaya, Ikvini; Hayati, Farida; Awaluddin, Rizki (Faculty of Medicine, Universitas Islam Indonesia, 2025)
Background: Purification of Centella asiatica methanolic extract using activated charcoal (ACP-CME) to isolate its non-aromatic compounds is a novel method that requires rigorous foundational safety data for the next validation stage.Objectives: The study aimed to determine the LC50 and identify toxicity signs of activated charcoal-purified Centella asiatica methanolic extract (ACP-CME) on zebrafish embryos.Methods: Fish Embryo Acute Toxicity (FET) was conducted following the 2013 standardized guidelines from OECD number 236. The zebrafish embryos were divided into eight groups (n=20/group), with an additional internal control in each group (n=4), namely 5 ACP-CME groups (ACP-CME at concentrations of 15.625, 31.25, 62.5, 125, and 250 ppm), a negative control group (distilled water), a positive control group (3,4-dichloroaniline), and a solvent control group (DMSO 0.2%). The observation was performed every 24 hours for 96 hours on four lethality parameters (coagulation, somite formation, tail-bud detachment, and visible heartbeat). The lethal concentration 50 (LC50) was calculated using Microsoft Excel 2019 to determine the signs and levels of toxicity of the extract based on the observational data. Results: ACP-CME exhibited concentration-dependent lethality caused by coagulation and absence of heartbeat, with 100% mortality at 250 ppm. Some abnormalities caused by ACP-CME exposure were spotted at concentrations of 31.25 and 125 ppm, with the occurrence of 15% and 10%, respectively.Conclusion: The LC50 of ACP-CME was 39.56 ppm. Malformation effects included lordosis, kyphosis, delayed tail-bud detachment, abnormal fin, somite formation failure, hatching failure, and yolk sac edema.